Answer:
5 minutes
Step-by-step explanation:
The first sentence → x - 2y = -1
the second one → 3x - 2y = -3
multiply the first one by -1
you can get → -x + 2y = 1
plus two sentences together
you can get → 2x = -2
so you are able to know that x = -1
and y = 0
Answer:
Step-by-step explanation:
$15 × 0.75 × 1.04 = $11.70
$25 × 0.75 × 1.04 = $19.50
$37 × 0.75 × 1.04 = $28.86
$65 × 0.75 × 1.04 = $50.70
9514 1404 393
Answer:
g(x) = √(x -5) +7
Step-by-step explanation:
To translate the graph of f(x) by h units horizontally and k units vertically, the function is transformed to ...
g(x) = f(x -h) +k
To translate f(x) = √x by 5 units horizontally and 7 units vertically, the function is transformed to ...
g(x) = √(x -5) +7